Acto de Inauguración del Ciclo Académico abril/agosto 2024 - Llivi Ruilova, Danny Vicente (2024)
On April 15 of the current year, the Inauguration Ceremony of the April/August 2024 academic cycle was held in the Auditorium Hall of the Faculty of Health and Human Sciences of the UEB; the same one that was attended by Dr. Silvana López Paredes; Doyenne; Mgtr. Maria Olalla; Mgtr. Cynthia Pilco Toscano; Mgtr. Maria Vallejo; responsible for the Nursing, Physical Therapy and Disaster Risk Engineering careers, in that order; Mgtr. Washington Fierro Saltos, director of Academic Management at the UEB; teaching staff and students.